Synthesis and Pharmacological Screening of Novel Non-acidic Gastroprotective Antipyretic Anti-inflammatory Agents with Anti-platelet Properties - Bruno, Olga; Schenone, Silvia; Ranise, Angelo; Barocelli, Elisabetta; Chiavarini, Milena; Ballabeni, Vigilio; Bertoni, Simona (Arzneimittelforschung, 2000)
The preparation and screening of antipyretic, anti-inflammatory, analgesic, gastroprotective and antiplatelet activities of original non-acidic aminobenzo-pyranopyrimidine derivatives are described. Major and dose-dependent analgesic and antipyretic properties were detected in all the compounds after oral administration (6.25-100 mg kg-1) in the mouse writhing test and in the E. coli lipopolysaccharide-induced fever in the rat, respectively. Unlike the reference drug Indometacin (ED50 ulcer = 9.1 mg kg-1), no gastrolesivity was displayed by all the new compounds up to 150 mg kg-1 so that therapeutical indices equal or higher than that of Indometacin were calculated. Furthermore, at 100 mg kg-1 they were able to prevent ethanol-induced gastric mucosal injury in rats. At a 1 mmol/l concentration the compounds under study were as effective as acetylsalicylic acid in inhibiting in vitro platelet aggregation induced by adenosine diphosphate.
Keywords: 2-Amino-5H-[1]benzopyrano[4,3-d]pyrimidin-5-amines; antiplatelet activity, gastroprotective activity, synthesis; Analgesics; Antiinflammatories; Antipyretics